Defense Mechanisms Styles of Relapsing Addicts in Malaysian Context - Abd. Halim Mohd Hussin; Farhana Sabri (2024)
Approaching defense mechanisms from the standpoint of drug addiction, it is proposed that defense mechanisms appear along the process of relapse. This study aims to determine the defense mechanism styles of relapsing addicts. A statistical description research design and cluster area sampling method was applied in sample choosing process. 135 respondents were involved in this study, which were randomly chosen from seven centers in East Coast and central zone of Peninsular Malaysia. The findings of the study indicate that neurotic defense mechanisms (M=12.46, S.D=2.14) are the most prominent amongst relapsing addicts, which undoing defense became a major defense style. These findings demonstrate that relapsing addicts employ multiple defense mechanisms styles and all these styles confirm the existence and nature of sub-culture in addiction. The use of defense mechanisms as emotional homeostasis amongst relapsing addicts indicates to incorporate the components of defense mechanisms in relapse prevention counseling.